The Influence of Manager Intention on Fraudulent Financial Reporting with Spiritual Quotient as Moderating Variable (Lembaga Penerbitan Unversitas Esa Unggul, 2022)
The purpose of this study is to examine the influence of manager intention on fraudulent financial reporting with a spiritual quotient as a moderating variable. Respondents in this study are managers who worked in Jakarta. The number of managers that were visited in this study was 33 managers from 13 companies. The method of determining the sample is by using the purposive sampling method, while the data processing methods used by the researchers are multiple regression and moderate regression analysis.The result shows that the variables of attitude toward behavior, norms subjective, and perceived behavioral control simultaneously influence manager intention. It is only attitude toward behavior and perceived behavioral control that influence manager intention significantly. Meanwhile, spiritual quotient can be a moderating variable for norms subjective and perceived behavioral control, but it can not be a moderating variable for attitude toward behavioral.